Prospective Unemployment and Interstate Population Movements: A Comment - Denton, Frank T. (The Review of Economics and Statistics, 1965)
turities on borrowing costs has little empirical support either. In addition, these results provide little support for the more conventional assertion that a lengthening of either contract lengths or loan-tovalue ratios is indicative of a reduction of borrowing costs to home buyers. Admittedly, the strongly negative coefficient of G in equation (3) suggests that something is wrong with my original equation.10 I find little merit, however, in Lee's contention that I used an improper measure of borrowing costs and that my estimate of the income elasticity of housing demand is substantially upward biased as a result.